Effects of Consistency in Healthcare Settings on Employee Performance in Zanzibar’s Public Health Facilities: An Analytical Study - HAJI, SHAABAN; Macha, Salvio; Mshenga , Mansour Maulid; Khamis , Asha Ussi; Kapaya, Saganga Mussa (International Journal of Scientific Research and Management (IJSRM), 2024)
This study investigates the impact of consistency on employee performance within Zanzibar's healthcare sector. Consistency, encompassing core values, agreement, and coordination/integration, is essential in maintaining high standards of care and ensuring alignment with organizational goals. Using a cross-sectional descriptive design and quantitative approach, data were collected from 288 healthcare employees with a minimum three-month tenure of the four selected district hospitals in Zanzibar through structured questionnaires, and responses were analysed using descriptive statistics and multiple regression analysis with the aid of IBM SPSS (Version 25).The results revealed that while consistency is a critical factor in organizational culture, its relationship with employee performance is weak and statistically insignificant. Specifically, the regression analysis indicates that an increase in consistency is associated with a slight decrease in employee performance, a finding that contrasts with previous studies. Despite this, the study identifies the importance of core values and coordination/integration as distinct constructs that contribute uniquely to organizational consistency.The study concludes that while consistency is important, its influence on employee performance may be more complex than previously understood. The findings suggest the need for targeted interventions to enhance specific aspects of consistency, such as cross-departmental coordination and management practices, to improve organizational effectiveness. Future research should focus on exploring these interventions and their impact on employee performance and patient care outcomes in healthcare settings.